Anastomotic leak after esophagectomy - Thakur, Binay; Yang, Ming; Bhandari, Nikesh; Sun, Zhenpin; Shrestha, Shashank; Kharel, Ashis; Neupane, Deewas; Thapa, Asha (Nepalese Journal of Cancer, 2023)
Background: Esophageal anastomotic leakage (AL) remains a frequent and feared postoperative complication, associated with high mortality and impaired quality of life. The aim of this study was to assess AL rates after esophagectomy with anastomosis at neck for esophageal and gastroesophageal junction cancer (GEJ), and compare the impact of AL on oncological outcome. Methods: Patients with squamous cell carcinoma and adenocarcinoma of esophagus/ gastroesophageal junction who underwent surgery between 2001-2018 were analyzed for cervical anastomotic leak. Results: 419 patients underwent esophagectomy with anastomosis placed at neck during 2001-2018. AL rate was 16%. AL was not found to be associated with anastomotic technique, surgical approach and technique, organ of conduit and route of conduit. A subgroup of patients (n=93) who had undergone neoadjuvant chemoradiation followed by surgery had AL of 30% vs 12% in rest of the treatment modality group (p<0.001). Median survival was 26 months and 34 months in patients with AL and without AL, respectively (p=0.03). AL was managed successfully in all patients. Conclusion: Cervical AL after esophagectomy for cancer of esophagus and GEJ can be treated successfully without major complications.